Capitalismo de plataformas: mi jefe es una App - Dinegro Martínez, Alejandra (2020)
Faced with the incessant development of technology and connectivity between markets, people and companies, a new model of doing business has emerged. Some call it “gig economy”, “sharing economy” and others, simply, platform capitalism. These business models are aimed at intermediating the demand for services or goods, of some people, with another sector of people that offer these services or goods in a quick, monitoring and simple way. Those who mediate this connection are digital platforms such as Uber, Glovo, Rappi, Beat, Airbnb, UberEats, among others; the same ones that have been assuming an interesting presence in Peru –in the last five years- as well as in Latin America and in various parts of the world. Being a new model, they present challenges and challenges, as well as blind spots that have been questioned when trying to answer some questions such as: should the relationship established between digital platforms and Apps with taxi drivers or delivery drivers be regulated? ¿O who takes responsibility if something goes wrong? This article describes the delivery apps model, presented as new, and how it has been introducing changes in traditional labor relations by varying important concepts such as: contract for “connection”, worker for “collaborator”, working hours with “I know your own boss”, salary for “service payment” or “dismissal for “account blocking”. Likewise, I comment on the experience of my brief participant research carried out in the city of Lima and how this business model reacts: ¿if it represents more of a risk or an opportunity, for people?